Agreement between PSMA-RADS and E-PSMA systems in classifying [18F]PSMA-1007 PET/CT lesions among prostate cancer patients: exploring the correlation between lesion size and uptake - Mendoza-Ávila, Miguel; Esparza-Pérez, Hiram; Castillo-López, Juan Andrés; Rodea-Montero, Edel Rafael (Frontiers in Medicine, 2024)
Purpose: To determine the agreement between the PSMA-RADS and E-PSMA standardized reporting systems in the classification of [ 18 F] 18 F-PSMA-1007-uptaking lesions identified on PET/CT scan in patients with prostate cancer (PCa) and post-prostatectomy who havewith suspected recurrent disease (local recurrence, regional nodal involvement and distant metastases), based on biochemical recurrencerecurrence or metastasis, while also exploring the correlation between lesion size and tracer uptake.Materials and Methods: A retrospective cross-sectional study of 32 post-prostatectomy prostate cancerPCa patients who had suspected recurrence recurrent diseaseor metastasis based on based on biochemical recurrence post-prostatectomy (prostate-specific antigen values that are 0.2 ng/mL or higher) their levels of prostate-specific antigen underwent [ 18 F] 18 F-PSMA-1007 PET/CT scan. The metastatic recurrent disease prostate cancerPCa lesions were characterized and subsequently classified using two standardized reporting systems (PSMA-RADS and E-PSMA). The lesions were grouped based on anatomical site, their size and SUVmax were compared using Kruskal-Wallis test with Dunn-Bonferroni post hoc tests. Spearman correlation coefficients were calculated between the size of the lesions and their SUVmax of the radiotracer [ 18 F] 18 F-PSMA-1007 for all the lesions and when grouped by anatomical site. Additionally, the agreement between lesion classifications was assessed using Cohen's kappa index.Results: Only 32 (69.98 ± 8.27, men) patients met the inclusion criteria, a total of 149 lesions with avid uptake of [ 18 F] 18 F-PSMA-1007 were identified. Positive correlation (r=0.516, p<0.001) was observed between the size of the metastatic prostate cancer lymph node lesions and their [ 18 F]18F-PSMA-1007 uptake. Substantial agreement was noted between the PSMA-RADS and E-PSMA classification system scores among all lesions (κ = 0.70, p < 0.001), with notable discrepancies primarily among lymph node lesions.. Conclusion: Our findings show revelead a positive correlation between the size of the metastatic prostate cancer lymph node lesions and their [ 18 F]18F-PSMA-1007 uptake, and although there is was substantial agreement between the PSMA-RADS and E-PSMA classification systems, there are were discrepancies mainly among the lymph node lesions.